Distributed Formation Control for Multiple Vertical Takeoff and Landing UAVs With Switching Topologies - Zou, Yao; Zhou, Zeqiang; Dong, Xiwang; Meng, Ziyang (IEEE/ASME transactions on mechatronics, 2018)
This paper proposes a distributed formation control approach for a team of vertical takeoff and landing (VTOL) unmanned aerial vehicles (UAVs) subject to switching topologies. The communication topology among UAVs is allowed to be with weak connectivity, in the sense of satisfying a uniformly jointly connected assumption. Since VTOL UAV systems are typically underactuated, a hierarchical framework is introduced such that a distributed control scheme can be established using neighboring positions and velocities. In particular, a distributed command force is developed to fulfill the formation objective, and an applied torque is synthesized for the attitude to track the command attitude. This command attitude is extracted from the command force by using a backstepping idea. In addition, an auxiliary system with appropriate parameters is introduced to preserve thrust saturation constraint, to guarantee nonsingular command attitude extraction and to avoid usage of neighboring acceleration information. With proper choices of Lyapunov functions, explicit selection criteria for the control parameters are formulated to ensure the asymptotic stability of the closed-loop system. Simulations and experiments are provided to validate the proposed theoretical results.